What is the safety case for health IT? A study of assurance practices in England. (December 2018) - Habli, Ibrahim; White, Sean; Sujan, Mark; Harrison, Stuart; Ugarte, Marta
Highlights: In-depth study of how clinicians and engineers analyse and justify Health IT safety risks. Strengths: establishment of a systematic approach to risk management and clinical engagement. Improvements: greater depth and clarify in hazard analysis and greater organisational support. Lack of publicly available examples of credible Health IT safety cases is a major deficit. Abstract: Objective: Health IT (HIT) systems are increasingly becoming a core infrastructural technology in healthcare. However, failures of these systems, under certain conditions, can lead to patient harm and as such the safety case for HIT has to be explicitly made. This study focuses on safety assurance practices of HIT in England and investigates how clinicians and engineers currently analyse, control and justify HIT safety risks. Methods: Three workshops were organised, involving 34 clinical and engineering stakeholders, and centred on predefined risk-based questions. This was followed by a detailed review of the Clinical Safety Case Reports for 20 different national and local systems. The data generated was analysed thematically, considering the clinical, engineering and organisational factors, and was used to examine the often implicit safety argument for HIT. Results: Two areas of strength were identified: establishment of a systematic approach to risk management and close engagement by clinicians; and two areas for improvement: greater depth and clarity in hazard analysis practices and greater organisational support for assuring safety. Overall, the dynamic characteristics of healthcare combined with insufficient funding have made it challenging to generate and explain the safety evidence to the required level of detail and rigour. Conclusion: Improvements in the form of practical HIT-specific safety guidelines and tools are needed. The lack of publicly available examples of credible HIT safety cases is a major deficit. The availability of these examples can help clarify the significance of the HIT risk analysis evidence and identify the necessary expertise and organisational commitments.